2016
DOI: 10.2147/ndt.s109768
|View full text |Cite
|
Sign up to set email alerts
|

Effects of perpetrator identity on suicidality and nonsuicidal self-injury in sexually victimized female adolescents

Abstract: PurposeChild sexual abuse and sexual dating violence victimization are common problems that are known to have long-term negative consequences. This study aimed to compare the sociodemographic, abuse-related, and clinical features of female adolescents who were sexually abused by different perpetrators, and identify the factors associated with suicidality and nonsuicidal self-injury (NSSI) in these cases.Patients and methodsData of 254 sexually abused female adolescents between the ages of 12–18 years were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…Indeed, sexually abused students had 2.63 times higher odds of suicidal ideation. Our findings are in line with studies showing a positive relationship between sexual abuse and suicidal behavior and ideation [ 41 – 43 ]. Furthermore, being sexually abused and negative mental health outcomes, such as depression, smoking and alcohol use, put adolescents at a greater risk of suicidal behavior [ 44 , 45 ].…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, sexually abused students had 2.63 times higher odds of suicidal ideation. Our findings are in line with studies showing a positive relationship between sexual abuse and suicidal behavior and ideation [ 41 – 43 ]. Furthermore, being sexually abused and negative mental health outcomes, such as depression, smoking and alcohol use, put adolescents at a greater risk of suicidal behavior [ 44 , 45 ].…”
Section: Discussionsupporting
confidence: 93%
“…A qualitative study examining the experiences of two Swedish young women who lived in violent relationships as teenagers showed that daily oppression and humiliation were internalized in the girls' self-perceptions, manifesting as lowered self-esteem, feelings of worthlessness, and loss of sexual pride (Wiklund et al 2010). Sexual dating violence in particular has been observed to be the strongest predictor of subsequent suicidal ideation in research on the effects of perpetrator identity in sexually victimized adolescent girls (Unlu and Cakaloz 2016). Studies have also found that the consequences of victimization vary by gender.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of this consideration was made evident by a study of the Office for National Statistic for England and Wales (2017) , which showed that more than half of adults who were molested during childhood experienced sexual abuse in later life and, in particular, suffered from domestic violence. Actually, CSA is a predictor of adult psychopathology, bringing about anxiety, fear and panic, personality disorders and psychiatric or psychological symptoms, sexualized behavior, sexual addiction or dissatisfaction or sexual maladjustment and disturbance, alcoholism and substance abuse, depression, dissociation, personality and eating disorders, feelings of isolation and stigma, low self-esteem, difficulty in trusting others, self-destructive behavior and suicide ( Alexander et al, 1998 ; Turell and Armsworth, 2000 ; Glover-Graf and Janikowski, 2001 ; Dube et al, 2005 ; Finkelhor et al, 2009 ; Fortier et al, 2009 ; Fergusson et al, 2013 ; Greenfield, 2014 ; Unlu and Cakaloz, 2016 ; Hannan et al, 2017 ; Papalia et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…This tendency has created an important gap in giving an adequate psychological answer to help-seeking women. Since research has already showed that the improvement of these studies could be useful to prevent re-victimization, thanks to specific treatments ( Unlu and Cakaloz, 2016 ; Seto, 2018 ). In our study, we wanted to check if the psychological effects of incest were considered by Italian centers supporting battered women, in order to acquire wider competence on the concrete strategies utilized in managing this problem.…”
Section: Introductionmentioning
confidence: 99%